THE EXISTENCE OF THE LIVING QUR'AN AND ITS CONTRIBUTION TO THE DEVELOPMENT OF RELIGIOUS MODERATION IN INDONESIA - Yusuf, Muhammad (Kopertais Wilayah X Jawa Tengah, 2024)
This article aims to analyze the existence and position of the living Qur’an as a new method of studying the Qur’an and its relevance to the development of religious moderation in Indonesia. As a preliminary study, this study applied two data collection techniques: documentation and observation. Documentation is used by taking material from various written sources regarding the living Qur’an. At the same time, the observations focused on several applications of the living Qur’an in learning in the study program of Al-Qur’an and interpretation and the applied research model. The collected data is classified by using a qualitative approach. The results show that both theoretically and practically, the living Qur’an method has been accepted as a new method or approach to studying the Qur’an. It is a method, approach, and model of Qur’anic studies. It also has a role in developing religious moderation and contributes to the development of religious moderation in Indonesia. What is certain is that with various terms, the living Qur’an has received a positive response among Qur’anic scholars in Indonesia. The living Quran is necessary to develop religious moderation, anticipate, and prevent the spread of radicalism that threatens the nation's disintegration in Indonesia.